2020
DOI: 10.1111/papr.12843
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural Adaptation and Psychometric Properties of the Greek Version of the Central Sensitization Inventory

Abstract: Objectives Recent studies support the opinion that central sensitization (CS) plays an important role in the pathophysiology of many chronic pain conditions. CS refers to hyperexcitability of the central nervous system, which can result in pain hypersensitivity and other somatosensory symptoms. Recognition of CS‐related symptomology is crucial in chronic pain evaluation and rehabilitation. The Central Sensitization Inventory (CSI) was created to evaluate symptoms that have been found to be associated with CS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 48 publications
10
29
0
Order By: Relevance
“…Support for the discriminant validity of the Serbian version of the CSI was provided by confirming the ability of total scores to discriminate among various types of chronically painful conditions and healthy controls, with presumably different levels of CS. Support for convergent validity of the CSI was provided by associations between CSI total scores, severity levels, and other CS‐related patient‐reported symptoms, including pain severity, sleep disturbance, cognitive functioning, pain catastrophizing, pain‐related fear‐avoidance beliefs, perceived level of disability, and perceived general mental and physical health, as has been found in previous studies 5–7 . The results of the present study provide additional support for the potential usefulness of the CSI in chronic pain assessment and treatment planning.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Support for the discriminant validity of the Serbian version of the CSI was provided by confirming the ability of total scores to discriminate among various types of chronically painful conditions and healthy controls, with presumably different levels of CS. Support for convergent validity of the CSI was provided by associations between CSI total scores, severity levels, and other CS‐related patient‐reported symptoms, including pain severity, sleep disturbance, cognitive functioning, pain catastrophizing, pain‐related fear‐avoidance beliefs, perceived level of disability, and perceived general mental and physical health, as has been found in previous studies 5–7 . The results of the present study provide additional support for the potential usefulness of the CSI in chronic pain assessment and treatment planning.…”
Section: Resultssupporting
confidence: 83%
“…The CSI has been psychometrically evaluated in English and other Asian, South American, and European languages. It has been found to be psychometrically sound in all published cross‐cultural studies to the present, with test‐retest reliability coefficients from 0.85 to 0.99 and Cronbach’s alpha from 0.88 to 0.99 5–7 . Evidence of convergent, discriminant, and predictive validity, using both subjective (eg, patient‐reported) and objective (including quantitative sensory testing, brain gamma aminobutyric acid levels, serum brain‐derived neurotrophic factor) CS‐related variables, have been found in a number of previous studies using multiple‐language versions of the CSI 5,8 .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous studies have shown good discriminative ability of the CSI to distinguish between chronic pain subjects and control subjects without pain [32][33][34]. Associations have been found between CSI scores and other validated patient-reported measures of CS-related symptoms, including depression symptoms, kinesiophobia, perceived disability, health-related quality of life, and sleep problems [26,27,30,33] Due to rationale linking chronic pain syndromes and fibromyalgia with postural control instability, it was hypothesized that there may be a potential relationship between higher CSI scores and postural control instability on a force plate. The force plate is mechanical sensing systems designed to measure the ground reaction forces and moments involved in postural control [36].…”
Section: Introductionmentioning
confidence: 98%
“…The CSI is considered the leading patient-reported outcome measure (PROM) for assessing CS-related symptomology [19]. Although it has a short, less than ten year history, the CSI has been translated and validated in adult populations into many languages, including Dutch [20], Spanish [21], Brazilian Portuguese [22], Gurajati [23], Serbian [24], French [25], Japanese [26], Greek [27], Nepalese [28], Russian [29], and Italian [30]. Additionally, the CSI has been validated in an adolescent population in European Portuguese [31].…”
Section: Introductionmentioning
confidence: 99%